Sistem Informasi Sumber Daya Manusia PT Perdana Maxxi International Berbasis Web - Richard; Ziveria , Mira (Research and Community Service UNIVERSITAS KALBIS, 2024)
PT Perdana Maxxi International is a logistic company that still uses conventional human resource system in processing employee data, attendance and leave, so it takes a long time to process it. This study aims to build a web-based human resource information system that includes the processing of employee attendance and employee leave with waterfall system development methods that included system anaylysis using cross functional diagram and cause-effect diagram, system design using Unified Modeling Language (UML), system development and programming using Hypertext Preprocessor (PHP) programming language and My Structure Query Language (MySQL) database and system testing using black box with alpha testing. The result of this study is a system that can be used to manage employee data, attendance and leave.